2012
DOI: 10.1002/adsc.201100600
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of Terminal Arylalkynes in Aqueous Medium by Ruthenium and Acid Promoted (RAP) Catalysis: Acetate‐ Assisted (sp)C(sp2)C Bond Formation

Abstract: The hexamethylbenzene ruthenium(II) dimer [{RuCl(μ‐Cl)(η6‐C6Me6)}]2 (5 mol%), tested among a series of ruthenium(II) and ruthenium(IV) complexes, represents an efficient precatalyst source for the dimerization of terminal arylalkynes ArCCH [Ar=C6H5, 3,4,5‐(OMe)3C6H2, 4‐MeOC6H4, 2‐MeOC6H4, 4‐MeC6H4, 2,4,5‐Me3C6H2, 4‐BrC6H4, 4‐ClC6H4, 4‐FC6H4, 4‐HC(O)C6H4, 4‐CH2CHC6H4, 3‐NCC6H4, 4‐O2NC6H4, 4‐EtO2C‐(CH2)3OC6H4, 4‐HO(CH2CH2O)3C6H4, 3‐HO(CH2CH2O)3‐C6H4] in acetic acid/water mixture (1:1, v/v). The reactions proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 119 publications
0
17
0
Order By: Relevance
“…However, considering selectivity toward cyclotrimerization, B was considerably worse compared to A. Although we did not further explore the reasons for this behavior, it is possible that the presence of trifluoroacetate ligands enhances the efficiency of the dimerization process [46].…”
Section: Catalytic Reactions Of Phenylacetylenementioning
confidence: 97%
“…However, considering selectivity toward cyclotrimerization, B was considerably worse compared to A. Although we did not further explore the reasons for this behavior, it is possible that the presence of trifluoroacetate ligands enhances the efficiency of the dimerization process [46].…”
Section: Catalytic Reactions Of Phenylacetylenementioning
confidence: 97%
“…25 The process proved most effective in acetic acid-water solvent mixtures, and reactivity was increased further by the addition of sodium acetate. These results suggested that the formation of an active alkynylruthenium species might have resulted from carboxylate-assisted deprotonation of a metal-coordinated terminal alkyne.…”
Section: Ruthenium Catalysismentioning
confidence: 99%
“…A plethora of stoichiometric and catalytic C–H functionalization reactions have been proposed to operate via a simultaneous metalation and intramolecular deprotonation pathway, usually referred to as a concerted metalation–deprotonation (CMD) mechanism . To understand the role of the acetate for selective C 5 -metalation, we undertook a computational study.…”
Section: Resultsmentioning
confidence: 99%